The Spirit of Moving Forward: An Overview of the Change Process in Sekolah Penggerak - Hasan, Kamaruddin; Krismanto, Wawan; Zainal, Zaid (Seminar Nasional LP2M UNM, 2024)
Abstract. This study aims to describe the change process in schools participating in the Program Sekolah Penggerak (PSP). The study adopts Michael Fullan's educational change theory framework, covering the stages of initiation, implementation, and continuity of change. Qualitative descriptive research methods are considered relevant to explore the perceptions of principals and teachers at Program Sekolah Penggerak regarding the stages of educational change in schools through PSP. Data were obtained through surveys, interviews, observations, and focus group discussions from six schools at Barru Regency, South Sulawesi, Indonesia. The results showed that most participants considered PSP a relevant innovation and was supported by various parties, such as internal schools, local governments, and local communities. This support facilitated the successful implementation of the program despite challenges, such as increased teacher workloads and inadequate infrastructure. At the continuity stage, the program was considered to have a significant positive impact on school management, teacher mindsets, and the quality of student learning. Participants also showed enthusiasm for continuing the program. In conclusion, PSP has brought significant changes to schools in Barru Regency. However, long-term success requires ongoing support from various parties and strict monitoring to ensure that the program has a significant and sustainable impact on the quality of the process and student learning outcomes. These findings provide several important implications for the program's sustainability, particularly in ensuring the sustainability of education transformation in Indonesia. Keywords: Education Change, Sekolah Penggerak, Education Transformation